Management of the Greek's ekistics and cultural heritage in Turkey - Eleni Gavra; Anastasia Bourlidou; Klairi Gkioufi (European Regional Science Association (ERSA), 2012)
Turkey constitutes a country privileged with ekistics and cultural heritage of crucial interest that is linked to ancient civilizations. Over the past decades, the turkish government has been formatting and developing a protective institutional framework, concerning the preservation of its historical environment. However, the country has endured many political and economical alterations that have influenced the qualitative character of the monumental architecture, as well as the regional development of historical communities. Ôhis paper deals with the Greek's cultural heritage in Turkey today, targeting on the enhancement of strategic solutions that concern the symbiosis of the dualism of greek origin ekistics heritage and tourism development in the turkish territories. The methodology approach is achieved through bibliography and in situ research and analysis that have taken place during a scientific research program concerning the Greek's cultural presence in Asia Minor (17th- 20th centuries). In addition to that, a thorough examination is followed in the evaluation of the existing turkish and international institutional framework, regarding the protection of the Greek's ekistics and monumental heritage in Turkey. In this context, a series of strategic measures is proposed in order to preserve and enhance the cultural value and aesthetics of the Greek's heritage in Turkey today. The governmental administration and international legislation, the elimination of bureaucratic issues, the promotion of strategic planning on both urban and architectural level, as well as the encouragement of the interstate relations between Turkey and Greece, are some of the potential solutions highly underlined in this paper.
Keywords: 330